Predictors of response to erenumab after 12 months of treatment. Issue 8 (16th July 2021) - Baraldi, Carlo; Castro, Flavia Lo; Cainazzo, Maria Michela; Pani, Luca; Guerzoni, Simona
Abstract: Objective: Erenumab is a monoclonal antibody acting against calcitonin gene‐related peptide receptor and approved for the preventive treatment of chronic migraine. The aim of the present study is to identify clinical predictors of good response in patients with chronic migraine and medication overuse‐headache. Material and methods: This was a retrospective single‐center not funded study. Enrolled patients were affected by chronic migraine and medication overuse‐headache treated with erenumab monthly, up to 1 year. At 1 year, patients were classified as good responders if they displayed a ≥50% reduction in the number of headache days per months compared to the baseline. Results: After 1 year, a significant improvement in the number of headache days per months, analgesic consumption, 6‐items headache impact test, and migraine disability assessment questionnaire scores were obtained compared to the baseline. Patients who obtained a ≥50% reduction in the number of headache days per month compared to the baseline displayed a longer history of medication overuse‐headache, a higher number of painkillers taken per month at the baseline and a higher number of failed preventive treatments in the past. Conclusions: Patients with longer medication overuse‐headache duration, higher analgesic intake, and a higher number of previous preventive treatment failures may receive less benefit with erenumab. Abstract : Patients affected by chronic migraine and medication overuse headache and treated with Erenumab for one year were more likely to be ≥50% responders if they had a longer duration of medication overuse‐headache, a higher number of painkillers taken per month and if had failed a higher number of preventive treatments for migraine.